Retrieval of non-sparse objects through scattering media beyond the memory effect. (21st July 2020) - Zhou, Meiling; Li, Runze; Peng, Tong; Pan, An; Min, Junwei; Bai, Chen; Dan, Dan; Yao, Baoli
Abstract: Optical imaging through scattering media is commonly constrained to sparse objects and the optical memory effect. To solve the problems, a method based on the combination of ptychography and the shower-curtain effect is presented here to achieve the retrieval of non-sparse samples through scattering media beyond the memory effect. The phase disturbance introduced by scattering media can be neglected based on the shower-curtain effect, and also the field-of-view can be extended via the ptychography. Results of the retrieval of hair-follicle cell from human skin demonstrate the effectiveness and feasibility of the proposed method for static and dynamic scattering media with the extended field-of-view to be 3.2 mm × 3.2 mm. The present work may be an approach for imaging through deep biological tissues.